Investigating the Impact of Psychological Distress on College Students - Devi, Naorem Sarita; Singh, Chungkham Lalit (Journal of Research in Vocational Education, 2026)
The primary purpose of this study is to gain knowledge about psychological issues that arise in students, especially while they are pursuing their academic goals and learning in an academic setting. The main psychological issues that affect students include anxiety, stress, sadness, and pressure. One of the main reasons of psychological issues among students is experiencing failures in their academic career. Other factors include learning difficulties, a lack of learning resources, negative family environments, and so on. When College students encounter these issues, it is crucial that they receive assistance in finding answers to their challenges. It is crucial that they implement the policies and initiatives in an acceptable way after receiving direction. In this study work, the causes of psychological difficulties, coping mechanisms for psychological problems, and recommendations have been the primary considerations.